Agenda Setting in the formation of Salamrejo Village Regulation Number 7 of 2016 concerning the Anniversary of Salamrejo Village, Kapanewon Sentolo, Kulon Progo Regency - Galuh Kusuma Ningtantri; John Chrysostomus Sado; Tanti Sadmawati; Kirana Rilla Pratama; Adji Suradji Muhamad (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The aim of this research is to provide an overview of the implementation of agenda setting in the formation of Salamrejo Village Regulation Number 7 of 2016 concerning the Anniversary of Salamrejo Village, Kapanewon Sentolo , Kulon Progo Regency. The research method used a qualitative descriptive method, namely an effort to collect, compile and interpret existing data and then analyze the data. The research concluded that the agenda setting process began with a more